Efektifitas Penggunaan Permainan Edukatif dalam Pembelajaran Perkalian di Kelas 4 SDIT Tahfidz Bintangku Kota Probolinggo - Afrilina Raudhotul Jannah; Siti Aisyah; Finuval Ahmad Faurudi; Nur Wiji Sholikin (PT Cendekia Education Center, 2026)
Multiplication learning at the elementary school level requires an approach that focuses not only on procedures but also on students' understanding of the concepts. One strategy used in education is the use of educational programs as components of learning activities. The purpose of this study was to analyze the effect of educational programs on the learning outcomes of fourth-grade students at SDIT Tahfidz Bintangku, Probolinggo City. This study was conducted on January 14, 2026, using a quantitative approach with a single-group pretest-posttest design. Thirty-three students were included in the study. The Wilcoxon Signed Rank Test was used to analyze the learning data because the data did not violate the assumption of normality. Furthermore, N-Gain analysis and effect size were used to enhance the interpretation of the research results. Keywords: Educational Games, Multiplication, Learning Outcomes, Elementary School